Definition of anatomical zero positions for assessing shoulder pose with 3D motion capture during bilateral abduction of the arms. Issue 1 (December 2015) - Rettig, Oliver; Krautwurst, Britta; Maier, Michael; Wolf, Sebastian
Abstract Background Surgical interventions at the shoulder may alter function of the shoulder complex. Clinically, the outcome can be assessed by universal goniometry. Marker-based motion capture may not resemble these results due to differing angle definitions. Methods The clinical inspection of bilateral arm abduction for assessing shoulder dysfunction is performed with a marker based 3D optical measurement method. An anatomical zero position of shoulder pose is proposed to determine absolute angles according to the Neutral-0-Method as used in orthopedic context. Static shoulder positions are documented simultaneously by 3D marker tracking and universal goniometry in 8 young and healthy volunteers. Repetitive bilateral arm abduction movements of at least 150° range of motion are monitored. Similarly a subject with gleno-humeral osteoarthritis is monitored for demonstrating the feasibility of the method and to illustrate possible shoulder dysfunction effects. Results With mean differences of less than 2°, the proposed anatomical zero position results in good agreement between shoulder elevation/depression angles determined by 3D marker tracking and by universal goniometry in static positions. Lesser agreement is found for shoulder pro-/retraction with systematic deviations of up to 6°. In the bilateral arm abduction movements the volunteers perform a common and specific pattern in clavicula-thoracic and gleno-humeral motion with maximum shoulder angles of 32° elevation, 5° depression and 45° protraction, respectively, whereas retraction is hardly reached. Further, they all show relevant out of (frontal) plane motion with anteversion angles of 30° in overhead position (maximum abduction). With increasing arm anteversion the shoulder is increasingly retroverted, with a maximum of 20° retroversion. The subject with gleno-humeral osteoarthritis shows overall less shoulder abduction range of motion but with increased out-of-plane movement during abduction. Conclusions The proposed anatomical zero definition for shoulder pose fills the missing link for determining absolute joint angles for shoulder elevation/depression and pro-/retraction. For elevation-/depression the accuracy suits clinical expectations very well with mean differences less than 2° and limits of agreement of 8.6° whereas for pro-/retraction the accuracy in individual cases may be inferior with limits of agreement of up to 24.6°. This has critically to be kept in mind when applying this concept to shoulder intervention studies.